2011
DOI: 10.1007/s12199-011-0225-y
|View full text |Cite
|
Sign up to set email alerts
|

Social network disruption as a major factor associated with psychological distress 3 years after the 2004 Niigata–Chuetsu earthquake in Japan

Abstract: Objectives The 2004 Niigata-Chuetsu earthquake of Japan caused a great deal of damage, and people living in the affected region are still struggling to reconstruct their lives. The aim of this study was to determine factors associated with psychological distress in people living in a town at the epicenter 3 years after the earthquake. Methods We conducted a cross-sectional study from June 2007 to January 2008. Participants included 225 individuals living in Kawaguchi (age C20 years) who reported psychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 16 publications
(22 reference statements)
5
61
0
Order By: Relevance
“…However, the present study was consistent with most other studies, which has indicated that prevalence of mental health problems is higher in younger or middle ages than older age [2], [8], [9]. In addition, our study has important implications for sex-specific intervention.…”
Section: Discussionsupporting
confidence: 92%
“…However, the present study was consistent with most other studies, which has indicated that prevalence of mental health problems is higher in younger or middle ages than older age [2], [8], [9]. In addition, our study has important implications for sex-specific intervention.…”
Section: Discussionsupporting
confidence: 92%
“…11 , 16 This may be due in part to financial burdens from house damage that adversely affect psychological health. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Social network disruption also emerged as a significant risk factor for psychiatric disorder in affected populations [11]. Among these predictors, sex was identified as an important variable significantly related to psychological distress.…”
Section: Introductionmentioning
confidence: 95%